(untitled) (Historia, 2021)
English A factor in the transition to democracy in South Africa during the period 1985- 1995 was a shift in the subjectivity of white South Africans, which was important in their acceptance of the process of change. New patterns of consumption and their attendant globalising cultural influences created selfreflexive forms of self-identity amongst whites which were inimical to mobilisation in nationalist and statist projects. This argument is developed through a case-study of the West Rand area in the transition period, focusing on the social role of entrepreneurs and retailers. The article surveys the course of the political conflicts in the area, showing how these impacted on business people. It then examines in detail a number of case-studies derived from interviews with business owners of the area in this period, which are used to illustrate the broader argument. Particular attention is given to the consumerist ethos and its interaction with the factors such as religion, ethnicity and the work ethic. Afrikaans Inkopies gedurende ‘n Revolusie: Entrepreneurs, Kleinhandelaars en “Wit” Identiteit in die Demokratiese Oorgangstyd ‘n Verskuiwing in die subjektiwiteit van wit Suid-Afrikaners was ‘n belangrike faktor in hulle aanvaarding van die proses van verandering tydens die SuidAfrikaanse oorgang na demokrasie in die periode 1985-1995. Nuwe verbruikerspatrone en hulle gepaardgaande globaliserende kulturele invloede het self-refleksiewe vorme van self-identiteit onder wit mense geskep wat mobilisering in nasionalistiese en staatsprojekte teengewerk het. Hierdie argument is ontwikkel deur ‘n gevallestudie wat gedurende die oorgangsperiode aan die Wesrand gedoen is. Dit het gefokus op die sosiale rol van entrepreneurs en handelaars. Die artikel lewer ‘n oorsig oor hoe die gang van politieke konflik in die area op besigheidsmense ingewerk het. Ten einde die breër argument te illustreer, volg ‘n gedetailleerde ondersoek na ‘n aantal gevallestudies, verkry uit onderhoude wat met besigheidseienaars in die area gevoer is gedurende die betrokke periode. Besondere aandag word gewy aan die verbruikersetos en die interaksie daarvan met faktore soos godsdiens, etnisiteit en werksetiek.